Managing Quality of Learning in Islamic Schools: An Analysis of Contributing Factors for Learning Toward Quality Improvement in Private Islamic Senior High Schools in Yogyakarta - Machali, Imam (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
This study examines how significant the contribution of the critical factors of learning in Islamic schools is which is cover to leadership, teachers’ competencies, infrastructures, and culture of the Islamic schools on learning quality and their impact on Private Senior High Islamic school students' satisfaction in Yogyakarta. This study implements a quantitative approach with a method of survey. The object study in Private Senior High Islamic school teachers in Yogyakarta with inclusion criteria of non-Civil Servant and has not qualified for teacher’s certification. The questionnaire is implemented in the data collection and analyzed with path correlation). The results of the study show that the transformational leadership model becomes a key factor in the development of Islamic schools. Mastery of four teachers’ competencies—pedagogy, professional, social, and personality—through various training has become key for the learning quality of the Islamic schools. Adequate Infrastructures, Islamic values-based Islamic schools ‘culture, and focusing their orientation on quality achievement and customer satisfaction have become the deciding factor for Islamic schools’ service quality. Keywords: Leadership, Teachers’ Competencies, Learning Quality, Customer Satisfaction